Réponses

2014-10-18T16:47:37+02:00
(2x +1) (x + 4) + (x + 4) (3 - 5x) = 0
(2x² + 8x + x + 4) + (3x - 5x² + 12 - 20x) = 0
2x² + 8x + x + 4 + 3x - 5x² + 12 - 20x = 0
- 3x² - 8x + 16 = 0

(x - 7) (3x - 5) + (9x - 4) (x - 7) = 0
3x² - 5x - 21x + 35 + (9x² - 63x - 4x + 28) = 0
3x² - 5x - 21x + 35 + 9x² - 63x - 4x + 28 = 0
12x² - 93x + 63 = 0
Meilleure réponse !
2014-10-18T16:49:14+02:00


Salut,

voici tes deux équations résolues.

Posons :

(1) : (2x + 1)(x + 4) + (x + 4)(3 - 5x) = 0

(2) : (x - 7)(3x - 5) + (9x - 4)(x - 7) = 0


(1) <=> (x + 4)[(2x + 1) + (3 - 5x)] = 0

(1) <=> (x + 4)(-3x + 4) = 0

A x B = 0 <=> A = 0 ou B = 0

x + 4 = 0 ou -3x + 4 = 0

x = -4 ou x = 4/3


(2) <=> (x - 7)[(3x - 5) + (9x - 4)] = 0

(2) <=> (x - 7)(12x - 9) = 0

A x B = 0 <=> A = 0 ou B = 0

x - 7 = 0 ou 12x - 9 = 0

x = 7 ou x = 3/4


Si tu as des questions, je reste dispo. A+